2013
DOI: 10.5581/1516-8484.20130027
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and sickle cell anemia

Abstract: Background Sickle cell disease, the most common hereditary blood disease in the world, is the result of an atypical hemoglobin called S (Hb S) which, when homozygous (Hb SS) is the cause of sickle cell anemia. Changes of puberty, correlated with a delayed growth spurt, begin late in both male and female sickle cell anemia individuals with repercussions on sexuality and reproduction. The objectives of this exploratory and descriptive study were to characterize the development of sexuality in adults with sickle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…There are few reports about this theme in SCD, many of them associated with priapism events (14-16) . All these facts reinforce the importance of the paper from Côbo et al published in this issue (17) .…”
supporting
confidence: 80%
See 1 more Smart Citation
“…There are few reports about this theme in SCD, many of them associated with priapism events (14-16) . All these facts reinforce the importance of the paper from Côbo et al published in this issue (17) .…”
supporting
confidence: 80%
“…Côbo et al (17) observed that individuals with SCD presented a limited knowledge of sexual facts, which may adversely contribute to sexual adjustment and to low self-esteem.…”
mentioning
confidence: 99%
“…People with SCD reported being treated as if they have a physical or cognitive impairment that will make them incapable of achieving goals and life milestones (Royal et al, 2011). They also reported stigmatizing experiences in intimate relationships, due to SCD complications, such as pain, priapism, and delayed puberty, impairing their sexuality (Cobo Vde, Chapadeiro, Ribeiro, Moraes-Souza, & Martins, 2013; Cole, 2007).…”
Section: Domainsmentioning
confidence: 99%
“…30 Sexuality and reproductive choices in women with SCD Information on sexuality in women with SCD is limited. [31][32][33] Given the well-described data on delayed puberty and adverse outcomes associated with pregnancy, how this knowledge may influence sexuality and reproductive decision making is relevant but unexplored. However, attitudes regarding contraception and unplanned pregnancy suggest that women with SCD are interested in avoiding pregnancy and use contraception, although at lower rates than the general population.…”
Section: Fertility In Womenmentioning
confidence: 99%